Role of Strategic Planning in Quality Enhancement of Higher Education Institutions: Case Study of Bamyan University - Mohammad Reza Ibrahim; Abdul Aziz Mohibbi (Eximia, 2024)
Afghanistan is a conflict-impacted country with a higher education sector that is undergoing rapid growth in the last two decades. The Ministry of Higher Education established the Quality Assurance & Accreditation Commission in 2009; and established the Quality Assurance & Accreditation Directorate (QAAD) in 2011. This body is to administer and oversee the accreditation process in all public and private HEIs of Afghanistan with a strategic outlook. By providing a comprehensive QA Framework and aiming to meet international standards; QAAD is functioning for Internal and External Quality Assurance of HEIs. This Framework emphasizes the development of a Strategic Plan for Higher Education Institutions in its first main criteria. Since QAAD and its relevant processes of Quality Assurance are newly implemented phenomena for the Higher Education Institutions; the processes of Developing Strategic Plans seem to be ineffective, challenging, and not used as a fundamental tool for quality enhancement. Furthermore, there are considerable challenges facing the implementation level of developed plans. Considering the important role of strategic planning in quality assurance; this study aims to evaluate the effectiveness and impacts of strategic planning on the processes of quality enhancement of Bamyan University as one of the National Higher Education Institutions. Nine major aspects of quality issues focusing on three main levels of strategic planning at the institution, Faculty, and Department are among the core subjects of this study. This study is carried out from the implementers’ point of view and includes the responses of all academic and non-academic members of Departments, Faculties, and Leadership of Bamyan University. Furthermore, this provides lessons learned and recommendations for institutions, policy makers, and other Higher Education Institutions. This study is conducted from February to August 2021 in Bamyan University of Afghanistan. A questionnaire was adopted and developed as the instrument of this study and nine major aspects of the qualification issues were included in the instrument. SPSS tool was employed to descriptively analyze the findings of the study. This study has shown that the exercise and experiences of strategic planning have not meaningfully and satisfactorily contributed to the enhancement of the quality of education of this University. The mean value of all aspects is somehow below average or average level. From the respondents’ point of view; the impact of strategic planning on quality assurance activities is greater than other aspects and this impact is lower in the sustainability of financial resources.